LC-UV/MS methods for the analysis of prochelator-boronyl salicylaldehyde isonicotinoyl hydrazone (BSIH) and its active chelator salicylaldehyde isonicotinoyl hydrazone (SIH) - Bureš, Jan; Jansová, Hana; Stariat, Ján; Filipský, Tomáš; Mladěnka, Přemysl; Šimůnek, Tomáš; Kučera, Radim; Klimeš, Jiří; Wang, Qin; Franz, Katherine J; Kovaříková, Petra (Journal of pharmaceutical and biomedical analysis, 2015)
Salicylaldehyde isonicotinoyl hydrazone (SIH) is an intracellular iron chelator with well documented potential to protect against oxidative injury both in vitro and in vivo. However, it suffers from short biological half-life caused by fast hydrolysis of the hydrazone bond. Recently, a concept of boronate prochelators has been introduced as a strategy that might overcome these limitations. This study presents two complementary analytical methods for detecting the prochelator-boronyl salicylaldehyde isonicotinoyl hydrazone-BSIH along with its active metal-binding chelator SIH in different solution matrices and concentration ranges. An LC-UV method for determination of BSIH and SIH in buffer and cell culture medium was validated over concentrations of 7-115 and 4-115 μM, respectively, and applied to BSIH activation experiments in vitro. An LC-MS assay was validated for quantification of BSIH and SIH in plasma over the concentration range of 0.06-23 and 0.24-23 μM, respectively, and applied to stability studies in plasma in vitro as well as analysis of plasma taken after i.v. administration of BSIH to rats. A Zorbax-RP bonus column and mobile phases containing either phosphate buffer with EDTA or ammonium formate and methanol/acetonitrile mixture provided suitable conditions for the LC-UV and LC-MS analysis, respectively. Samples were diluted or precipitated with methanol prior to analysis. These separative analytical techniques establish the first validated protocols to investigate BSIH activation by hydrogen peroxide in multiple matrices, directly compare the stabilities of the prochelator and its chelator in plasma, and provide the first basic pharmacokinetic data of this prochelator. Experiments reveal that BSIH is stable in all media tested and is partially converted to SIH by H2O2. The observed integrity of BSIH in plasma samples from the in vivo study suggests that the concept of prochelation might be a promising strategy for further development of aroylhydrazone cytoprotective agents.
Keywords: Chromatography, Liquid; senzitivita a specificita; Sensitivity and Specificity; Drug Stability; referenční standardy; Spectrophotometry, Ultraviolet; hydrazony; Boronyl salicylaldehyde isonicotinoyl hydrazone; Stability; zvířata; molekulární struktura; Culture Media; potkani Wistar; Molecular Structure; kultivační média; Reference Standards; kyseliny isonikotinové; Isonicotinic Acids; kyseliny boronové; chromatografie kapalinová; Rats, Wistar; Male; Hydrazones; Prochelator salicylaldehyde isonicotinoyl hydrazone; chelátory; spektrofotometrie ultrafialová; stabilita léku; Aroylhydrazone; aldehydy; Animals; Boronic Acids; Pharmacokinetics; mužské pohlaví; Aldehydes; hmotnostní spektrometrie; Chelating Agents; Mass Spectrometry